Heavy Metal, Arsenic, and Selenium Concentrations in Bird Feathers from a Region in Southern China Impacted by Intensive Mining of Nonferrous Metals. (31st December 2019) - He, Chao; Su, Tongping; Liu, Shilong; Jiang, Aiwu; Goodale, Eben; Qiu, Guangle
Abstract: Heavy metal pollution is widespread in China, particularly in its mining regions. Mercury (Hg) concentrations in birds from Guizhou Province were recently reported to be above adverse effect levels, even in nonmining areas. We sampled birds to investigate whether Hg might be a threat near lead (Pb), zinc (Zn), and tin (Sn) mines in Guangxi Zhuang Autonomous Region. We measured concentrations of 8 metals/metalloids in feathers of 627 resident birds representing 60 species sampled across 14 sites on 5 rivers. We found that Hg concentrations (mean ± standard deviation, 1.27 ± 2.02 ppm) were lower than in the recent Guizhou study. Mercury had the fewest correlations with other metals/metalloids; the mined metals (Pb, Sn, Zn) had the most such correlations. Levels of cadmium (Cd; 1.12 ± 2.64 ppm), arsenic (As; 4.78 ± 17.11 ppm), and Pb (17.18 ± 24.49 ppm) were closer to thresholds of adverse effects or relatively high compared to other studies. With the exception of a few hot spots for Hg, Cd, and As near mines, metal/metalloid levels were fairly evenly distributed among sites, consistent with the regional occurrence of mineable ore deposits. It appears that Hg is not threatening to all avian species in China, although it may be problematic for some species near Hg mines. In addition to Hg, however, other metals/metalloids may pose wildlife health hazards. Environ Toxicol Chem 2020;39:371–380. © 2019 SETAC